Doped, conductive SiO2 nanoparticles for large microwave absorption. Issue 1 (December 2018) - Green, Michael; Liu, Zhanqiang; Xiang, Peng; Liu, Yan; Zhou, Minjie; Tan, Xinyu; Huang, Fuqiang; Liu, Lei; Chen, Xiaobo
Abstract Although many materials have been studied for the purpose of microwave absorption, SiO2 has never been reported as a good candidate. In this study, we present for the first time that doped, microwave conductive SiO2 nanoparticles can possess an excellent microwave absorbing performance. A large microwave reflection loss (RL) of −55.09 dB can be obtained. The large microwave absorption originates mainly from electrical relaxation rather than the magnetic relaxation of the incoming microwave field. The electrical relaxation is attributed to a large electrical conductivity that is enabled by the incorporation of heterogeneous (N, C and Cl) atoms. The removal of the magnetic susceptibility only results in a negligible influence of the microwave absorption. In contrast, the removal of the heterogeneous atoms leads to a large decrease in the electrical conductivity and microwave absorption performance. Meanwhile, the microwave absorption characteristics can be largely adjusted with a change of the thickness, which provides large flexibility for various microwave absorption applications. Nanoscience: microwave absorption Doped nanoparticles of silica (SiO2 ) have been found to act as a very strong absorber of microwave radiation. A US-Chinese collaboration of scientists discovered that, unlike pure SiO2 nanoparticles, those doped with atoms of N, C and Cl induce a reflection loss at large as −55 dB at a frequency of around 7 GHz. The doped nanoparticles, which measured 4–8 nm in diameter, were fabricated by slowly adding the precursor tetraethyl orthosilicate (TEOS) to the solventN, N '-dimethylformamide (DMF) and then adding hydrazine monohydrochlorid. The resulting solution was then heated, washed and dried. The resulting nanoparticles were then dispersed in paraffin wax rings and the permittivity and permeability measured in the 1.0–18.0 GHz range using a network analyzer. The team attributes the strong microwave absorption to the doped nanoparticles' good electrical conductivity.